Fast charging infrastructure for electric vehicles: Today's situation and future needs. (July 2018) - Gnann, Till; Funke, Simon; Jakobsson, Niklas; Plötz, Patrick; Sprei, Frances; Bennehag, Anders
Highlights: Real-world fast charging data from Sweden and Norway is analyzed. Model is created to determine the ratio of BEVs and fast charging points. The ratio of BEVs to public fast charging points can be similar to conventional fuel. Charging power and battery size of vehicles determine results the most. Fast charging can become economically viable very quickly. Abstract: Potential users of plug-in electric vehicles often ask for public charging facilities before buying vehicles. Furthermore, the speed of public charging is often expected to be similar to conventional refueling. For this reason, research on and political interest in public charging focus more and more on fast charging options with higher power rates, yet estimates for future needs are rare. This paper tries to fill this gap by analyzing current charging behavior from a large charging data set from Sweden and Norway and take the findings to calibrate a queuing model for future fast charging infrastructure needs. We find that the ratio of battery electric vehicles to public fast charging points can be similar to other alternative fuels in the future (close to one fast charging point per 1000 vehicles for high power rates of 150 kW). In addition, the surplus on the electricity prices for payoff is only 0.05–0.15 €/kWh per charging point. However, charging infrastructure needs highly depend on battery sizes and power rates that are both likely to increase in the future.